An Early Reference to DNA Barcode for the Anacardiaceae Family - Alberto Ryadi; Iskandar Siregar; Carina de Melo Moura; Oliver Gailing; Fitri Yola Amandita (HAYATI Journal of Biosciences, 2023)
Anacardiaceae is well-known for its edible fruits and economically important species in Indonesia. Approximately 3% of Indonesia's endangered and vulnerable species belong to this family. Fast and accurate species identification is crucial to support the conservation efforts for this family, such as employing DNA sequences. Species identification using DNA sequences, known as DNA barcoding, has been widely used in many applied fields. So far, the application of DNA barcoding for Anacardiaceae plant species is limited to several genera only, such as Mangifera and Spondias. This research aimed to enrich the DNA barcode references of Anacardiaceae and to evaluate the most suitable and effective genetic marker as DNA barcodes to identify species of 35 samples representing sixteen species of the Anacardiaceae family using chloroplast markers matK and rbcL as barcode regions. When comparing the morphological identification with the molecular assignments, the barcode accuracy was 62.50% (matK), 60.61% (rbcL), and 73.33% (matK+rbcL) at the genus level. All the markers failed to show a barcoding gap, even though the t-test showed that the intraspecific and interspecific genetic distances were significantly different for matK and rbcL+matK. Among others, Gluta walichii (Hook.f.) Ding Hou and Melanochyla caesia Jack were the only species successfully resolved by all markers. Nevertheless, new DNA barcodes of six Anacardiaceae species were made available by this study, enriching the genetic references of tropical flora diversity.